2017
DOI: 10.7863/ultra.16.04071
|View full text |Cite
|
Sign up to set email alerts
|

Fetal Lymphatic Malformations: More Variable Than We Think?

Abstract: Lymphatic malformations are benign lesions that result from abnormal development of the lymphatic and venous systems. These lesions may be detected during routine prenatal ultrasound screening, and typically demonstrate imaging findings of a multiseptate cystic lesion lacking solid components, vascularity, and calcifications. We report 73 cases of prenatally detected lymphatic malformations and describe greater variability in their prenatal sonographic appearance than previously reported, including purely cyst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 24 publications
1
15
0
Order By: Relevance
“…At US, these malformations appear as multiseptated cystic lesions, lacking solid components, vascularity and calcifications. However, a recent review has described a greater imaging variability than previously reported, including mixed cystic/solid lesions and occasional calcifications [17].…”
Section: Congenital Lymphatic Malformationsmentioning
confidence: 92%
See 3 more Smart Citations
“…At US, these malformations appear as multiseptated cystic lesions, lacking solid components, vascularity and calcifications. However, a recent review has described a greater imaging variability than previously reported, including mixed cystic/solid lesions and occasional calcifications [17].…”
Section: Congenital Lymphatic Malformationsmentioning
confidence: 92%
“…Lymphatic malformation is the most often detected vascular malformation in the fetus and the most widely described in the literature [4,[15][16][17][18]. The reported incidence is 1:2,000-6,000 cases in live births, with a slight male predominance [16].…”
Section: Congenital Lymphatic Malformationsmentioning
confidence: 99%
See 2 more Smart Citations
“…Yet, it has become well known that lymphatic malformations may have a very complex and atypical appearance. Oliver et al describe a greater than previously reported variability in the prenatal sonographic appearance of these lesions 75 . Authors introduce a new classification of lymphatic malformations that categorizes the lesions by their internal architecture.…”
Section: Vascular Malformations Spectrummentioning
confidence: 99%